Analisis Proyeksi Laporan Keuangan Perusahaan Penerbangan Saat Transisi PSAK 30 Menjadi PSAK 73 - Erika Annisa Damayanti; Putri Nur Asri; Rangga Wishnu Wardhana; Asril Naufal Diaz; Muhammad Ari Gunawan (CV. Ulil Albab Corp, 2022)
This study aims to predict the emergence of new regulations in accounting research. Especially the existence of PSAK 73 will replace PSAK 30 in terms of Leases. This study provides an estimate if the new regulations will be implemented. PSAK 73 changes the form of the double accounting system into one, which means leases are not classified and are calculated using two methods such as capital leases and operating leases. It uses a capital lease calculation and is classified as a structural asset. Assets are recognized and then depreciated. The results of this study indicate that the conversion from PSAK 30 to PSAK 73 affects the entity's income statement. Unit costs increase due to additional interest expense and depreciation. Assets also increased, so the asset management ratio and profitability ratio both decreased.